MEKANISME PENYAKIT HATI DALAM AL-QUR’AN DAN KORELASINYA DENGAN PSIKOLOGI KLINIS: PENDEKATAN TAFSIR ILMI - Ikhlash Hidayatullah; Ali Akbar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This article aims to explore the concept of diseases of the heart in the Qur’an through a thematic exegesis. The discussion focuses on identifying the linguistic, theological, and psychological dimensions of spiritual illness as described in selected Qur’anic verses such as Al-Baqarah [2]:10, Al-Mā’idah [5]:52, Al-Ahzāb [33]:32, and Al-Mutaffifīn [83]:14. The study adopts a qualitative descriptive method using library research, emphasizing the interpretive synthesis of classical and contemporary exegesis, including al-Ṭabarī, al-Rāzī, Ibn Kathīr, and Quraish Shihab. The findings reveal that maradh al-qalb represents not only emotional or moral corruption but also an epistemological deviation that disrupts one’s spiritual perception and ethical orientation. Furthermore, the Qur’an identifies arrogance, hypocrisy, envy, and lust as major symptoms of heart disease, all of which weaken faith and moral consciousness. The article concludes that purification of the heart (tazkiyat al-nafs) through dhikr, repentance, and adherence to divine guidance is an essential process in restoring human spiritual health and achieving qalbun salīm (a sound heart).